In Vitro Screening of Fungicides Against Phomopsis viticola and Diaporthe perjuncta - Mostert, L.; Denman, S.; Crous, P.W. (South African Journal of Enology and Viticulture, 2017)
Phomopsis viticola is the cause of Phomopsis cane and leaf spot disease of grapevines, while Diaporthe perjuncta is associated with bud mortality. The efficacy of nine fungicides (azoxystrobin, flusilazole, folpet, fosetyl-Al + mancozeb, kresoxim-methyl, mancozeb, penconazole, spiroxamine and trifloxystrobin) against isolates of P. viticola and D. perjuncta was determined in vitro using the mycelial growth test. Additionally, azoxystrobin, folpet, kresoxim-methyl, mancozeb, propineb and trifloxystrobin were tested for their ability to inhibit spore germination in vitro. Ten isolates of P. viticola and three of D. perjuncta were used in the mycelium inhibition tests, and five isolates of P. viticola in the spore germination tests. The effective concentration at which mycelial growth was inhibited by 50% and at which 50% of the spores (EC50 value) were inhibited from germinating was calculated for each isolate/fungicide combination. In the mycelium growth test flusilazole, penconazole and trifloxystrobin gave better inhibition at lower concentrations than folpet and fosetyl-Al + mancozeb. No significant differences in the mean ECso values were detected among azoxystrobin, flusilazole, kresoxim-methyl, penconazole, spiroxamine and trifloxystrobin. There were also no significant differences among the mean EC50 values of azoxystrobin, kresoximmethyl and mancozeb. Flusilazole and penconazole inhibited mycelial growth at the lowest mean EC50 values obtained. Kresoxim-methyl and trifloxystrobin inhibited spore germination at lower concentrations than folpet or mancozeb. Folpet required the highest concentration to inhibit 50% germination and was significantly different from mancozeb and propineb. There were also no significant differences among the mean EC50 values of mancozeb, propineb and azoxystrobin. The mean EC50 values of the strobilurin fungicides were not significantly different from one another. These results indicate that the strobilurin fungicides inhibited mycelial growth and spore germination of P. viticola. Trials need to be conducted to verify these findings under field conditions.